Interacting With a Visiting Dog Increases Fingertip Temperature in Elderly Residents of Nursing Homes - Nilsson, Anne; Handlin, Linda; Lidfors, Lena; Petersson, Maria; Uvnäs-Moberg, Kerstin (Frontiers in Psychology, 2020)
Aim: to investigate whether interacting with a visiting dog influences fingertip temperature and cortisol levels in residents living in nursing homes for the elderly. The study included two groups, the dog group (n=13) and the control group (n=11-15) and lasted for 8 weeks for the dog group and 6 weeks for the control group. All participants were residents living at nursing homes for the elderly. The researchers visited small groups of the participants twice weekly during the entire study in both the dog and the control group. The visiting dog and the dog handler accompanied the researchers during weeks 3-6. Fingertip temperature was measured and saliva samples for cortisol determination were collected at 0, 20 and 60 minutes for the dog group and at 0 and 20 minutes for the control group. For analysis the study was divided into periods; Period 1 (week 1-2), Period 2 (week 3-4), Period 3 (week 5-6) and Period 4 (week 7-8, only the dog group). Mean values based on all data obtained at 0 and 20 minutes during period 1-3 were compared between groups. A second, separate analysis for the dog group also included data from 60 minutes and for period 4. For the dog group fingertip temperature increased significantly between period 1 and 2, 1 and 3 and 1 and 4 (p<0.05) . In addition, fingertip temperature rose significantly between 0 and 20 minutes and between 0 and 60 minutes within all periods. For the control group a significant decrease in fingertip temperature was observed between period 1 and 3 (p<0.05). Fingertip temperature did not differ between the two groups during period 1, but was significantly higher for the dog group than for the control group during periods 2 and 3 (p<0.05 and p<0.001, respectively). Cortisol results are only presented descriptively due to that many samples had too low volume of saliva to be analyzed. In the present study interaction between elderly residents and a visiting dog resulted in increased fingertip temperature, probably reflecting a decrease in the activity of the sympathetic nervous system and therefore a decrease in stress levels.